Mental Health Status and Its Determinants Among Nursing Staff in Saudi Arabia: An Analytical Review - Alzahrani, Bashayer Abdullah Radad (Saudi Journal of Medicine and Public Health, 2025)
Introduction: Nursing is inherently stressful; globally, practitioners report high rates of psychological distress. This review synthesizes literature from 2015–2024 to analyze the prevalence and unique cultural-systemic determinants of mental health issues among Saudi Arabian nursing staff. Methods: A systematic literature search was conducted across PubMed, Scopus, and regional databases using keywords like "nurse," "burnout," and "Saudi Arabia." Peer-reviewed quantitative and mixed-methods studies focusing on clinical and primary care settings between 2015 and 2024 were included and analyzed for prevalence, associated factors, and professional outcomes. Results: Elevated mental health symptoms are pervasive among Saudi nurses: anxiety prevalence ranges from 20–60%, depression from 10–55%, and burnout particularly emotional exhaustion reaches 80% in high-acuity settings. Pandemic-related spikes saw stress levels reach 61%. Primary determinants include excessive workloads, staffing shortages, and long night shifts. Sociodemographic factors such as gender and nationality significantly influence outcomes; while some findings vary, elevated distress is notably reported among Saudi nationals and males in certain contexts. High distress levels are directly linked to increased medical errors, absenteeism, and compassion fatigue, ultimately compromising the quality of patient care. Conclusion: Mental health disorders are widespread among Saudi nurses, driven by workplace pressures and cultural variables. Enhancing workforce well-being requires organizational reforms such as optimized staffing and managerial engagement combined with individual resilience training and accessible counseling to ensure healthcare sustainability.